Perbedaan Pola Komunikasi Generasi X dan Generasi Y Dalam Hubungan Pernikahan - Aryanti, Nathania Trixie; Chairil, Augustin Mustika (Universitas Prof. Dr. Moestopo (Beragama), 2025)
Generation X and Generation Y couples have different ways of communicating, influenced by generational differences caused by technological developments. The pattern of communication in couples of Generation X and Generation Y is formed due to the gradual openness. Good communication in relationships will create harmony. This study uses qualitative methods, which aim to understand, analyze, and interpret phenomena in depth through the description of words. The Data in this study were collected by purposive sampling technique, where the data were taken based on the criteria of informants in accordance with the objectives of the study. In Generation X couples, social media is not used as a means in their marriage relationship, in contrast to Generation Y couples who more often face conflicts due to misunderstandings through social media. However, both generations still prioritize face-to-face communication directly in their marriages. Harmony in relationships is created by mutual understanding and mutual commitment between partners. Overall, this study emphasizes the importance of understanding the different ways of communication between Generation X and Generation Y to improve relationships and reduce conflicts that may arise from different ways of communicating.